The Islamic Gifted Curriculum Framework: Conceptualising Gifted Education From Islamic Perspective - Mahiz Spawi; Ahmad Fuad Mohamad Amin; Zulkarnin Zakaria; Abdel Rahman Ibrahim Suleiman Islieh; Wan Ahmad Zakry Wan Kamaruddin; Mohd Zamrus Mohd Ali; Rossidi Usop (Scientific Research Publishing Inc., 2024)
Indexed by ERA